2004 chronic obstructive pulmonary disease with and without bronchiectasis in Aboriginal Australians: a comparative study. Issue 12 (22nd December 2020) - Heraganahally, Subash S.; Wasgewatta, Sanjiwika L.; McNamara, Kelly; Mingi, Joy J.; Mehra, Sumit; Eisemberg, Carla C.; Maguire, Graeme
Abstract: Background: Chronic respiratory disorders are highly prevalent in Aboriginal Australian population, including chronic obstructive pulmonary disease (COPD) and bronchiectasis. However, there is paucity of information in the literature among Aboriginal patients with underlying COPD with and without bronchiectasis. Aims: In this retrospective study we evaluated the demographic and clinical characteristics of adult Aboriginal Australian patients with a clinical diagnosis of COPD with and without bronchiectasis from the remote communities of the Northern Territory of Australia. Methods: Clinical records were reviewed to extract information on demographics, respiratory and medical comorbid conditions, COPD directed treatment, hospital admission frequency and exacerbations. Chest radiology were reviewed to evaluate the presence or absence of bronchiectasis. Spirometry results, sputum culture and cardiac investigations were also recorded. Results: Of the 767 patients assessed in the remote community respiratory outreach clinics 380 (49%) patients had a clinical diagnosis of COPD. Chest X‐ray and computed tomography scan were available to evaluate the presence of bronchiectasis in 258 patients. Of the 258/380 patients, 176/258 (68.2%) were diagnosed to have COPD alone and 82/258 (31.8%) had bronchiectasis along with COPD. The mean age was 56 and 59 years among patients with and without bronchiectasis, respectively, and 57% were males with bronchiectasis. Patients with bronchiectasis had lower body mass index (22 vs 24 kg/m 2 ), frequent hospital admissions (2.0 vs 1.5/year) and productive cough (32.1% vs 28.9%). Spirometry showed 77% had forced expiratory volume in 1 s (FEV1 )/forced vital capacity ratio <0.7. In 81% and 75% of patients with and without bronchiectasis the FEV1 /forced vital capacity ratio was <0.7 and the mean FEV1 was 39% and 43% respectively. Conclusions: About 32% of Aboriginal Australians had co‐existent bronchiectasis with COPD. Lower body mass index, productive cough, frequent hospital admission and marginally more severe reduction in lung function were noted among patients with COPD and bronchiectasis compared to those with COPD in isolation.